Hydrogen Sulphide Strategy in Oil and Gas Field: Review - Abubaker Abdalsamed, Ihssin; Ali Amar, Ibrahim; Ahmed Al-abbasi, Aisha; K. Ahmied, Elfitouri; Abduallah Farouj, Abdusatar; Ali Kawan, Jamal; Ali Awaj, Mohammed (Scientific Journal for Faculty of Science-Sirte University, 2023)
Hydrogen sulphide (H2S) is one of the most hazardous substances in oil and gas production fields when it comes to the risks posed by its presence. H2S is a naturally occurring gas found within oil, gas reservoirs, and sewage water. Chemically the gas is extremely toxic, flammable, and corrosive to different materials. H2S can strongly cause material cracking and environmental pollution and a reduction in oil quality. Thus, prevention measures are very important to produce gas containing even low levels of H2S. The prevention requires chemical treatment to remove H2S or convert the gas to an acceptable compound. Therefore, a big challenge was faced to develop a new technological method to manipulate H2S problems. This review evaluates strategies for crude oil desulfurization by reviewing desulfurization literature. In addition, the effects of hydrogen sulfide on metals and metal protection will be outlined. Finally, some perspectives on the effects of H2S on personnel health and safety will be discussed.